(untitled) (Research, Society and Development, 2021)
Objective: To analyze the daily life and experiences of children and adolescents with diabetes mellitus, insulin users, during school time. Methodology: Study with a quantitative approach carried out in 2021. The participants were insulin users who attend or attended a school environment. An online questionnaire with questions about treatment and school life was used. Results: Of the 105 survey participants, 41.90% were diagnosed with less than eight years of age; 30.50% use a syringe for insulin administration; 74.50% apply insulin during the school period and among these, 59.10% have autonomy in the application and 60% identified embarrassment in applying the medication in the school institution; 57.14% reported having compromised school performance due to DM complications; 73% indicate that the school institution is not prepared to assist students during the clinical complications of DM; 62.85% report the discontinuity of the diet during the school period and 35.23% had some problem during school trips. Conclusion: The lack of preparation in schools hinders the management of students with DM and encompasses several factors: difficulty in emergency care in case of hypoglycemic and hyperglycemic crises; the lack of knowledge of professors and other employees to help with the application of insulin and other needs; the misinformation of other students and the difficulty on school trips. It is of great importance that the school is prepared to receive these students and their demands, and for this it requires the commitment of the family, health team and school for the training of education professionals.